2003
DOI: 10.2527/2003.8182019x
|View full text |Cite
|
Sign up to set email alerts
|

Fermented and nonfermented liquid feed to growing pigs: Effect on aspects of gastrointestinal ecology and growth performance

Abstract: The effect of feeding dry feed (DF), nonfermented liquid feed (NFLF), and fermented liquid feed (FLF) to growing pigs on aspects of gastrointestinal ecology and on performance was investigated. Nonfermented liquid feed was prepared by mixing feed and water at a ratio of 1:2.5 immediately before feeding. Fermented liquid feed was prepared by mixing feed and water in the same ratio as NFLF, and stored in a tank at 20 degrees C for 4 d, after which half the volume was removed twice daily at each feeding and repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
210
7
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(248 citation statements)
references
References 22 publications
30
210
7
1
Order By: Relevance
“…There is a plethora of data to indicate that liquid feeding of pigs may significantly reduce production costs, improve growth rates, time to slaughter, lower feed to gain ratio or a combinations of these performance parameters besides offering welfare benefits (Braude 1967 and1971;Jensen and Mikkelsen, 1998;Lawlor et al, 2002;Canibe and Jensen, 2003;Scott et al, 2007). However, there has been little new work on liquid feeding in growing-finishing modern porcine genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a plethora of data to indicate that liquid feeding of pigs may significantly reduce production costs, improve growth rates, time to slaughter, lower feed to gain ratio or a combinations of these performance parameters besides offering welfare benefits (Braude 1967 and1971;Jensen and Mikkelsen, 1998;Lawlor et al, 2002;Canibe and Jensen, 2003;Scott et al, 2007). However, there has been little new work on liquid feeding in growing-finishing modern porcine genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The concepts of non-fermented liquid feeding (NFLF) and fermented liquid feeding (FLF) have been well described by Canibe and Jensen (2003). Liquid feeding of pigs can significantly reduce production costs as it allows the use of low, dry matter by-products and can, to some extent, offer welfare benefits under hot, summer conditions (Scott et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is consistent production of research studies showing that the gains associated with feeding FLF are marginal, at best (e.g. Lawlor et al, 2002;Canibe and Jensen, 2003;Canibe et al, 2007). The lack of consistency between experimental designs make direct comparisons, and logical interpretation, of the many studies difficult (Plumed-Ferrer and von Wright, 2009).…”
Section: Fermented Liquid Feedsmentioning
confidence: 99%
“…It has been reported that feeding certain probiotic strains to pigs could improve growth performance, prevent the growth of pathogenic bacteria and reduce the incidence of diarrhea (Shu et al, 2001;Gardiner et al, 2004;Taras et al, 2006;Casey et al, 2007). At the same time, feeding an FLD prepared with the use of bacteria, such as lactic acid bacteria, has also been shown to improve pig performance and to reduce the number of enteric pathogens (Canibe and Jensen, 2003;Stein and Kil, 2006). These positive influences may be due to the low pH, high short-chain fatty acid content and high lactic acid bacteria content of the FLD.…”
Section: Introductionmentioning
confidence: 99%